Thermal-Hydraulic-Mechanical coupling analysis using FLAC3D-TOUGH2 for an in situ heater test at Horonobe underground research laboratory. Issue 5 (3rd September 2019) - Kwon, Sangki; Lee, Changsoo
ABSTRACT: It is an urgent issue in many countries utilizing nuclear energy to develop a safe disposal technique for heat-generating high-level radioactive waste (HLW). Because of the decay heat from the radioactive waste and the high pressure from in situ stress, thermal stress, hydraulic pressure, and swelling pressure from bentonite buffer, the engineered barriers surrounding the canister will experience complex Thermal-Hydraulic-Mechanical (THM) coupling behaviors. The development of a reliable THM coupling analysis technique is a critical task for HLW disposal. In this study, FLAC3D and TOUGH2 were integrated for three-dimensional THM analysis. Integration of the data from Thermal-Mechanical analysis using FLAC3D and Thermal-Hydraulic analysis via TOUGH2 allowed an efficient simulation of the THM behaviors. The analysis technique was applied to an in situ experiment carried out at Horonobe URL. During the modeling, the variations of THM properties including thermal conductivity, specific, heat, Elastic modulus, relative permeability, etc., due to the change in water content were considered. In the deposition hole, compressive stress of about 1.7 MPa was developed. It is possible to observe that the bulk modulus was distributed from 35MPa to 2.5 MPa due to the variation of water content. Sand layer installed between buffer and rock played as a dominant flow path.